2014
DOI: 10.2478/aep-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Coal Cleaning Versus the Reduction of Mercury and other Trace Elements’ Emissions from Coal Combustion Processes

Abstract: Samples of steam coal used in heat and power plants as well as densimetric fractions obtained on a laboratory scale by dense organic liquid separation have been examined. The contents of ash, mercury, chromium, cadmium, copper, nickel and lead have been determined in coal, in the light and medium fraction as well as in the refuse. The degree of removal of mineral matter and the examined heavy metals as well as the coal combustible parts yield have been determined. Examination of 5 coals revealed that it is pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…This could be obtained in the coal washing process, which is well known and commercialized (Rallo et al 2012 ). The possibility of removing significant amounts of mercury from coal in this process was confirmed in the following studies: Dziok et al ( 2015b ), Zajusz-Zubek and Konieczyński ( 2014 ), Pan et al ( 2017 ), and Pyka and Wierzchowski ( 2016 ). However, the effectiveness of mercury removal from coal is varied and it is closely related to the mode of mercury occurrence in coal.…”
Section: Introductionmentioning
confidence: 75%
“…This could be obtained in the coal washing process, which is well known and commercialized (Rallo et al 2012 ). The possibility of removing significant amounts of mercury from coal in this process was confirmed in the following studies: Dziok et al ( 2015b ), Zajusz-Zubek and Konieczyński ( 2014 ), Pan et al ( 2017 ), and Pyka and Wierzchowski ( 2016 ). However, the effectiveness of mercury removal from coal is varied and it is closely related to the mode of mercury occurrence in coal.…”
Section: Introductionmentioning
confidence: 75%
“…The soil in the urban areas (residential areas, parks, roadsides) usually has low or medium-high magnetic susceptibility, also in other regions of the world (Lu and Bai, 2006;Aguilar-Reyes et al, 2011Magiera et al, 2013). Burning coal in home furnaces and small boiler rooms in the residential areas is still the main source of the dust pollution in Poland and in many countries that utilize coal as their main energy resource (Konieczyński and Stec, 2009;Zajusz-Zubek and Konieczyński, 2014;Hławiczka et al, 2001). In the Rybnik area, the percentage of the particulate matter from the flat heating processes (in the general concentration of the dust coming from various emitters) was as much as 49% in (Hławiczka et al, 2012.…”
Section: Lateral Changesmentioning
confidence: 98%
“…However, due to the new Best Available Techniques (BAT) Conclusions for large power plants (BAT-LCP 2017 ) approved by the European Commission in April 2017, which tighten up the SO 2 emission standards and introduce restrictions on the emission of mercury (Hg) into the atmosphere, it will be necessary to improve the quality of coal used for combustion processes (Makowska et al 2017b ). Several studies (Akers and Dospoy 1994 ; Zhu et al 2015 ; Makowska et al 2014 , 2016 ; Dziok et al 2014 ; Zajusz-Zubek and Konieczyński 2014 ) have shown that the coal cleaning processes constitute an effective method for removing ecotoxic elements (such as Hg) from coal, thereby lowering the emission of these elements to the environment in the processes of combustion, gasification, and pyrolysis. On the other hand, the waste produced during coal cleaning can pose a threat to the environment because of the accumulation of ecotoxic elements mostly in this waste.…”
Section: Introductionmentioning
confidence: 99%